Peningkatan Kosakata Bahasa Arab melalui Media Teka Teki Silang Bergambar di Kelas V SD Al Ashriyyah Nurul Iman Parung- Bogor - Parhan, Parhan; Safii, Mohamad; Rozaq, Abdul (Ta'limi | Journal of Arabic Education and Arabic Studies, 2023)
This study aims to obtain an overview of the implementation of the use of Pictorial Crossword Puzzles in improving Arabic Vocabulary for fifth grade students of SD Al Ashriyyah Nurul Iman Ds. Waru Jaya Kec. Parung Kab. Bogor Province West Java. This research is a classroom action research which consists of two cycles, each cycle includes planning, implementation, observation, and reflection. The data collection techniques used in this study were tests, observations, interviews, and documentation. Based on the results of the research that has been carried out, it shows that Pictorial Crossword Puzzle Media can increase the Arabic vocabulary of fifth grade students of SD Al Ashriyyah Nurul Iman Ds. Waru Jaya Kec. Parung Kab. Bogor Province West Java. The increase in Arabic vocabulary for fifth grade students of SD Al Ashriyyah Nurul Iman Ds. Waru Jaya Kec. Parung Kab. Bogor Province West Java, can be seen from memorization and pronunciation, intonation, application, sentence structure, writing lafadz. From the results of the action research conducted by the researcher, it can be concluded that the Arabic vocabulary of the fifth grade students of SD Al Ashriyyah Nurul Iman Ds. Waru Jaya Kec. Parung Kab. Bogor Province West Java by using the application of Pictorial Crossword Puzzles to increase significantly. The students are more enthusiastic and focused in carrying out Arabic learning activities